Fundamentals of Iot Communication Technologies - Herrero, Rolando (USA : Springer, 2022)
This textbook explores all of the protocols and technologies essential to IoT communication mechanisms. Geared towards an upper-undergraduate or graduate level class, the book is presented from a perspective of the standard layered architecture with special focus on protocol interaction and functionality. The IoT protocols are presented and classified based on physical, link, network, transport and session/application layer functionality.
Keywords: Communication; Iot; Technologies